(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The paper reconstructs the personnel and budget of the Aragonese chancellery in Naples between 1456 and 1473, until now unknown to the literature, through the expenses of ten account books of the royal great seal. Secretaries and writers were paid from the seal rights paid by the beneficiaries of letters sent from the chancellery. The information contained in the seal books, which were destroyed in 1943 (except for a single book and some fragments), was reconstructed thanks to the insertions in the receipts (quietanciae) requested by Antonello Petrucci of Aversa, who was the recipient of the seal rights and later the first secretary of the kingdom, and the handwritten files of some scholars. We also focus on the operating of the chancellery of Alfonso the Magnanimous during his stay in the kingdom, with attention to its functional and physical dislocation into different scribanias. Thanks to the reconstruction of the chancellery’s budget we can explain why in 1490 the humanist Giovanni Pontano, Petrucci’s successor, submitted his resignation to King Ferrante of Aragon